Redesign Marketing Mix in Hj Karmi's Chili Chips Based on Consumer Perception and Digital Concept - Septya, Fanny; Agbolosoo, John Atsu; Yusri, Jumatri; Pitri, Susila (Jurnal AGRISEP, 2025)
Hj. Karmi chilli chips, a small enterprise in Dumai City, Riau, Indonesia, is contending with competition from local competitors. This research seeks to revitalize the marketing mix by examining consumer perceptions and digital strategies. The study assesses consumer views on the 7Ps marketing mix (product, price, place, promotion, process, people, physical evidence) for Hj. Karmi chilli chips. This study examines the present condition of these elements and proposes improvements to boost competitiveness and facilitate market growth. Utilizing survey methods with 40 participants and descriptive analysis based on the Likert scale and gap analysis, the study discovered that consumers have a very positive perception of price, people, and process, and a positive perception of place and product. Consumers rated physical evidence and promotion as average. Overall, the marketing perception of Hj. Karmi's consumers are positive. The product features simple packaging that emphasizes the product itself. The chips are priced competitively in Dumai City, providing affordable quality. The store's location suffers from poor accessibility and parking. Limited promotional activities have led to low awareness. Family members manage operations, allowing for close oversight but restricting growth. Consumers highly rate the production process for its quality and hygiene. The physical evidence was considered unattractive. Enhancements are necessary in product, place, promotion, people, and physical evidence to boost competitiveness. Recommendations include enhancing product quality and packaging, improving store accessibility, increasing digital promotion, hiring non-family employees, and upgrading the store layout to attract consumers in Dumai City, Riau.